Evaluating a self-proclaimed successful Dutch supply chain partnership - Venselaar, Marieke (A+BE | Architecture and the Built Environment, 2018)
This study aims to reflect on experiences of professionals from a Dutch housing association and a contractor who perceive their relation as a successful supply chain partnership (SCP). Employing a narrative approach, this study shows the subgrouping in informal relations within and around the successful supply chain. The subgrouping shows examples of visible and hidden power dynamics. We conclude that, although the perception of success may have positive spin-offs, the members are not always positive about each other, SCP is applied to only a limited part of the client’s internal supply chain, SCP is applied in an arbitrary way that not always seems to be fair, and continuation of the success in the future is uncertain. The study provokes many practical interventions, but the main recommendation is to keep reflecting on informal relations to address some of the social issues.